Report of an Audit of Irish Research on Child Protection 1990-2009 - BUCKLEY, HELEN; CORRIGAN, CARMEL; KERRINS, LIZ (Children Acts Advisory Board, 2010)
Executive Summary 1. Introduction The Children Acts Advisory Board (the CAAB) 1 is responsible for advising the Minister for Health and Children and the Minister for Justice, Equality and Law Reform on policy issues relating to the coordinated delivery of services to children and young people at risk under the Child Care Act, 1991 and the Children Act, 2001. In 2009 the CAAB commissioned the Children?s Research Centre, Trinity College Dublin to conduct an audit of Irish child protection literature. The study has two keys outputs, a database containing information from the research included in the audit and a report summarising the key points from the analysis of the database, information on funding sources and appropriate conclusions. The methods used to identify relevant research were database and internet searches and stakeholder consultation. This included searching academic journal databases and relevant organisational databases, and internet searches using key terms and words, collating literature already known to and held by the research team, formally communicating by email and telephone with stakeholders and inviting them to suggest relevant literature, reading the bibliographies/reference lists of relevant books, book chapters, journal articles, policy documents, and reports of commissions/inquiries to identify research that met the inclusion criteria. Information on the allocation of funding for child protection research in the Republic of Ireland in specified years was obtained by contacting research funders directly. 2. Key Findings A total of 190 research documents were identified in line with the criteria agreed between the researchers and the CAAB, and are included in the audit. The key findings from the analysis of the audit are as follows: Research identified in the audit has tended to focus on child protection and the child protection system generally, as well as sexual abuse. This research has primarily been undertaken by clinicians and academics, and spans across sectors. Over half, (110 or 58%) of the research falls under the heading of policy/practice reviews/analysis. This is further reflected in the fact that the research most commonly focused on operating 1 Formerly the Special Residential Services Board (SRSB) Report of an Audit of Child Protection Research in Ireland 1990-2009. ii procedures, followed by practice issues and the policy framework, both in studies with a single focus and those with multiple foci. The most common type of publication was peer reviewed article (74 or 39%), with commissioned research accounting for just 7% (13). This is in line with the findings that 68% (128) of commissioning/publishing bodies and 74% (139) of research bodies were in the academic sector. The research published and/or commissioned by the statutory sector follows the pattern found in the audit generally, with the most common type of study being policy/practice review/analysis (27 or 48%) and the most common focus being operating procedures (22 or 39%). Information sources rarely incorporated primary research with children, with only 14 studies (8%) citing direct contact with children and young people. Information on children was more commonly gathered from case files, professionals and family members. The topics covered in the identified research were very wide-ranging but closely related to the primary subject area (type of abuse) and the sector in which the research was located. 3. Gaps Identified in the Research The Extent to Which Research is Available on the Different Areas of Child Abuse The audit shows that the main focus of research appears to be on cross subject research followed by child sexual abuse. It should be noted here that the vast majority of cross subject research does not refer to the study of the combination of specific forms of abuse (such as physical and sexual abuse). Rather it refers to research that is located in the broad area of child abuse and child protection and does not address specific forms of abuse but instead these studies critically examine or review the child protection system. While neglect is the most commonly reported form of child abuse, the proportion of research on the topic is quite low when compared with the proportion of research on child sexual abuse. Physical and emotional abuse are each reported marginally less often than child sexual abuse but appear to be under-researched as specific topics. The Extent to which Research Provides Cross Sectoral Coverage of Child Abuse Issues There is a clear emphasis in child protection policy on inter-agency and inter-disciplinary working, as evidenced in policy and strategy documents. It would appear desirable, therefore that a cross sectoral approach is taken in relation to child protection as this can contribute to and draw on inter-agency and inter-disciplinary working, as well as providing more comprehensive and holistic analysis of issues and potential solutions. However, the audit shows that inter-agency and inter-disciplinary research on child abuse is relatively limited. Report of an Audit of Child Protection Research in Ireland 1990-2009. iii The Extent to Which Research Answers Key Questions for Policy and Practice Examining the factors most commonly associated with child abuse reports and placement of children in out of home care shows that the most frequently reported type of concern is child neglect but the audit shows that only 3% (5) of the research materials focused on this. Child sexual abuse is the third most frequently reported type of child abuse about which the highest amount of research material is published. However, it is not possible to judge whether the materials are adequate or sufficient without a comprehensive assessment of the needs of policy makers and practitioners. Nevertheless, it could be reasonably inferred that the comparatively low number (7) and percentage (4%) of material on physical abuse and the lack of material on emotional abuse are inadequate to answer key questions for policy and practice. Furthermore, only 6% (12) of the materials offer profiles of victims of child abuse, only 5% (9) of the materials focus on the experiences of children and families who are users of the child protection services and only 6% (12) of the materials identified in the audit covered programme and service evaluations. There is a shortage of research on `what works? and sources of information on the most useful interventions and programmes with which to address the identified problems in the Irish context. The Degree of Research Quality and the Extent of Confidence in Research The quality of the research in the audit appears to be somewhat uneven. While it was not always clear that a piece of material, apart from journal articles, had been peer reviewed, it could be estimated that up to 50% of the content had not been subject to external quality assurance. There are particular shortcomings in statistical data on child protection and welfare in Ireland, as follows: There is no single source, publication or website that gives comprehensive information about the incidence and prevalence of child abuse, including the gender and ages of the children, the causal or associated factors and the numbers of children that died from child abuse. Data recorded on child abuse reports are not recorded consistently. Published service level indicators give very limited scope for analysis, e.g. the broad sources of reports of abuse and service outcomes for children in terms of immediate results and medium term impacts. National statistics reveal no epidemiological trends, merely the number of new reports year on year and they give no sense of the prevalence, or recurrence, of different types of child abuse, the length of interventions or the resource implications of service provision in different types of cases. They do not make any linkages between social factors affecting families and the incidence of child abuse and thereby do not identify vulnerability factors. Report of an Audit of Child Protection Research in Ireland 1990-2009. iv Restricting the collection of data about child protection to reports made to the statutory child protection system is limiting and consequently the comprehensiveness of these data is questionable. The Extent to Which Research is Accessible While a number of research databases already exist in Ireland and elsewhere, the entire content is not always available for viewing or downloading. Of the materials in the current audit, approximately 75% (approximately 140 documents) are not available without purchase at individual or institutional level. 4. CONCLUSIONS Based on the available material our conclusions are as follows. 1. While the audit has identified an amount of material on child protection from a number of disciplines, the volume and coverage of Irish research does not appear to be commensurate with the current national concern about this problem and the challenges being faced by policy makers and service providers in the following respects. There is a shortage of good quality, robust research on child protection practice in the statutory sector, particularly in respect of social work, which is acknowledged to be central to child protection. There is a shortage of child protection-focused research on the factors that cause and perpetuate child abuse, such as homelessness, addiction, parental mental illness and domestic violence. The need for material on these areas is demonstrated by the nature and scale of reports to the child protection system and the removal of some children from their families into out of home care as a result of the above mentioned adversities. There is a shortage of research on the profile and characteristics of child victims or studies that involve children as active participants in, as opposed to objects of, research. The audit illustrates a shortage of evaluative studies that demonstrate the impact of interventions and `what works? in child protection.Report of an Audit of Child Protection Research in Ireland 1990-2009. v 2. There have been some very useful developments in research dissemination and supporting access to research, particularly by the OMCYA and the HRB, but this audit shows that the majority of the Irish research material is not publicly accessible beyond abstract formats, a factor that limits its usefulness. The lack of professional peer reviewed journals and outlets for publication in Ireland, particularly for social work research, also limits dissemination. The production and public availability of systematic reviews of existing research, by topic, would facilitate greater take-up and utilisation. 3. While a number of relevant and important topics have been the subject of commissioned research, there is currently no integrated research agenda on child protection although the OMCYA is currently developing a children?s research agenda. The current lack of such an integrated agenda reflects the ad hoc funding arrangements that have existed to date. National statistics on the nature of child abuse reports indicate that neglect and associated problems should take priority in this agenda. The implementation of The Agenda for Children?s Services and the creation of the HSE as one body under which health and welfare services operate provide more opportunities for co-ordinated research commissioning and dissemination. 4. Available statistical data on child protection, which are vital for planning services and allocating resources, require further development and analysis to improve accuracy and to provide a more comprehensive picture of child protection issues and activities. For instance, the source of referrals, the type of adversities being experienced by families, the interventions being made and their impact on children. The above conclusions are based on the objectives underpinning this project, which were to identify and develop a database of Irish child protection literature, identify the main sources of funding and identify gaps in research as demonstrated by the audit of literature available. The database that has been developed will require updating to reflect new additions and hopefully will provide a useful resource to policy makers and service providers. While this audit revealed a number of shortcomings in the availability and accessibility of Irish research, the project represents an important step in bringing together existing material and should provide a starting block for the development of a national agenda for research on child protection. Such a task will require a wider scoping exercise that encompasses the views of all stakeholders in the sector, reflects international developments on the topic, and considers child protection as one dimension of the wider context and continuum of child welfare, from prevention to out of home care.
PUBLISHED
Keywords: CHILD PROTECTION; EVIDENCE BASED PRACTICE